Dust (Total Suspended Particulate) Exposure Risk Assessment in Unit Packer PT. X - Siswati, Siswati; Diyanah, Khuliyah Candraning (JURNAL KESEHATAN LINGKUNGAN, 2018)
Dust (Total Suspended Particulate) is one type of air pollutant that often found. Dust exposure in long time can cause health problems. The purpose of this study is to analyze the risk of dust exposure in the Unit Packer PT X. This research is descriptive using Environmental Health Risk Assessment (EHRA). The variables were dust hazard identiï¬ cation, dose-response analysis, exposure analysis, and risk characteristics. The average dust concentration in Packer Unit 7.01 mg/m3 so it was below the TLV (Threshold Limit Value) of the Health Minister Decree of The Republic of Indonesia No. 1405/Menkes/SK/XI/2002 concerning Requirements and Environmental Health Ofï¬ ce Work Industry. Intake received the largest individual that is on Packer Unit 1 is 0.621 mg/kg/day and RQ > 1, which means the population is has a risk for non-carcinogenic effects in the next 30 years. In addition, the presence of dust in the workplace can cause effects inconvenience in work and when inhaled for a long time can also be a negative impact on the health of the workforce. So that, it needed to control as a preventive measure such as maintain the ï¬ lters dust, reduce the number exposure by wearing personal protective equipment (PPE) such as respirators (anti-dust masker), and reducing the duration of dust exposure such as employee work rotation to other unit.